THE RESPONSE OF THE ALBANIAN COMPETITION AUTHORITY TO THE COVID-19 CRISIS (EU and comparative law issues and challenges series (ECLIC), 2021)
The outbreak of COVID-19 pandemic was a shock for the global economy. It affected almost every country, but certainly in developing countries its impact was harder. The immediate effect was the shortage of several medical and paramedical equipment which were necessary to prevent the virus spread. This shortage was felt in Albanian markets as well and was rapidly followed by a sharp increase of prices in paramedical products. The consumers suffered the highly increased prices amongst fear that in absence of these products, their life was threatened. This behaviour of the market participants was considered suspicious by the Competition Authority which decided to initiate a preliminary investigation to find out whether this behaviour was abusive, or it normally reflected the sudden shortage and the state of emergency. The instigation of this procedure was based on several complaints reported in the media and complaints directly submitted by consumers to the Competition Authority. At the first glance, the traders were exploiting the health emergency to maximise their profits. Subsequently, the Competition Authority (CA) decided to apply some preliminary measures on the wholesale market operators. Furthermore, the CA intervened even in a case of a company in dominant position which was furnishing selected pharmacies. These interventions aimed at restoring somehow the distorted competition in paramedical and medical products. This article will try to shed light on the current market situation and on the effectiveness of the interventions of the CA. How should the Competition Authority behave to restore the distorted competition? Are the current introduced measures enough to help all market participants overcome this state of health emergency? These questions and other issues related with the peculiar situation will be addressed in the current article. The article will be organized as follows: First, a glimpse of the regulation of Albanian competition law will be given. Second, the situation under COVID-19 emergency will be elaborated taking into consideration the guidelines of Communication of the Commission on “Temporary Framework for assessing antitrust issues related to business cooperation in response to situations of urgency stemming from the current COVID-19 outbreak” (2020/C 116 I/02). Lastly, the evaluation of the measures introduced by the Competition authority will be analysed and recommendations will be provided.